Virtual Classroom Competences Required by Electrical Installation and Maintenance Works Trade Teachers in Technical Colleges in Yobe State, Nigeria - Fwah, Karnilius Gideon; Idowu, Adebayo John; Dasofunjo, Abiodun (Asian Journal of Science, Technology, Engineering, and Art, 2024)
This study investigated the virtual classroom proficiencies needed by Electrical Installation and Maintenance Works trade teachers in Technical Colleges in Yobe State, Nigeria. Employing a descriptive survey research design, the population of the study was 69 individuals, comprising 53 teachers and 16 ICT experts from eight Technical Colleges in Yobe State, Nigeria. Due to the manageable size of the population, the entire population was included in the study, eliminating the need for sampling. Data collection utilized the "Technical Colleges Virtual Classroom Competency Questionnaire (TCVCCQ)," structured with responses on a 5-point scale. Validation of the instrument was performed by three experts from the Department of Electrical/Electronic Technology Education, Federal College of Education (Technical), Potiskum, Yobe State, resulting in a reliability index of 0.82 determined through the Cronbach Alpha technique. Mean statistics were employed to analyze data for the research questions, while hypotheses were tested at a significance level of 0.05 using a t-test. The findings revealed a lack of proficiency among teachers in utilizing participant panels and video play features within virtual classrooms. The study recommends that principals arrange in-house workshops for teachers to acquire requisite proficiency in using participant panel features, and further suggests consultation with video experts to enhance the quality of instructional videos for improved utilization of video play features within virtual classrooms.